EFEKTIVITAS MELACAK INFORMASI RAWI DI ERA NEW MEDIA :(KOMPARASI APLIKASI JAWĀMI‘ AL-KALIM, MAKTABAH SYĀMILAH, HADITHENCYCLOPEDIA, DAN DORAR.NET) - Binti Khabibatur Rohmah Al Arifah; Alifia Rizqa Unzila; Muhammad Fathun Niam (CV. Adiba Aisha Amira, 2025)
Today's technological developments make human work easier, one of which is in hadith tracking, as well as tracking the degree of hadith. Tracking the biography of the narrator is an important aspect in assessing an incoming hadith. These biographies were previously compiled in books that needed to be searched for manually. From the above reality, regarding technological advances and raw materials in the aspect of hadith sanad, this study aims to, firstly, explain and provide and clarify the limitations regarding at-tarikh al-ruwah in hadith science. Secondly, to trace the biography of the rawi by utilising access from two desktop applications Jawāmi' Al-Kalim v4.5, Maktabah Syāmilah v4.0 2023, mobile applications, Hadith Encyclopedia v18.4.0, and the website dorar.net. To achieve these objectives, this study uses library research to gather information about the object of study and simulate hadith tracking in related applications. The results of this study show: first, that at-tarikh al-ruwakh is a branch of the science of ar-rijal al-hadis that traces the biographies of the rawis. Secondly, the Jawāmi' Al-Kalim v4.5 software provides more detailed rawi information than the other three, from general information, information on the narrator's teacher, the narrator's student, to references used by the developer.